Geology of the Northwestern Krania Basin - Caplan, Charlotte A; Gildersleeves, Helen C.; Harding, Al G.; Harris, Benedict J. R.; Johnson, Benedict W. W.; Kershaw, James A.; Maltby, Matthew J. (Bulletin of the Geological Society of Greece, 2019)
We present a new map of 30 km2 of the northwestern Krania Basin at 1:10,000 scale, including rocks of the Pindos Ophiolite Group and associated units, and the sedimentary fill of the Krania Basin. The Krania Basin is a flexural basin developed in the Middle – Late Eocene and filled first with alluvial fan conglomerates and later with turbidite sandstones and siltstones, following a deepening of the basin. Analysis of the clasts within the sediment, combined with paleoflow analyses, suggest sediment input from the eroding Pindos Ophiolite to the west. The Pindos Ophiolite Group is represented in the area by pillow lavas, sheeted dykes and serpentinized harzburgites of the Aspropotamos Complex. The ophiolite forms imbricated, thrust bounded blocks which show two phases of thrusting, corresponding to Late Jurassic and Eocene stages of ophiolite emplacement. We identify five stages of deformation within the basin itself, starting with Early - Middle Eocene syndepositional extensional faulting associated with the formation of the basin. This was followed by four stages of post-depositional deformation, starting with Late Eocene compression associated with basin closure, which caused thrust faulting and folding of the sediments. Oligocene dextral faulting with a thrust component affected the basin margins. Finally, two normal faulting events with different orientations have affected the basin since the Miocene.